2013
DOI: 10.1128/aem.00819-13
|View full text |Cite
|
Sign up to set email alerts
|

Pleiotropic Effects of GacA on Pseudomonas fluorescens Pf0-1 In Vitro and in Soil

Abstract: Pseudomonasspecies can exhibit phenotypic variation resulting fromgacSorgacAmutation.P. fluorescensPf0-1 is agacAmutant and exhibits pleiotropic changes following the introduction of a functional allele. GacA enhances biofilm development while reducing dissemination in soil, suggesting that alternative Gac phenotypes enablePseudomonassp. to exploit varied environments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
30
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 40 publications
10
30
1
Order By: Relevance
“…These sRNAs bind to the global regulator RsmA, releasing its repression of genes necessary for biofilm formation 20,40 . The decrease in biofilm formation observed upon CRISPRimediated silencing of gacS is in agreement with the regulatory model and with phenotypes observed in gacS mutants in various Pseudomonas 17,18,25,40,68 . In SBW25, GacS is also regulating genes involved in oxidative stress response, and the gacS::Tn5 mutant has a reduced capacity to survive exposure to sub-lethal doses of H2O2 25 .…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…These sRNAs bind to the global regulator RsmA, releasing its repression of genes necessary for biofilm formation 20,40 . The decrease in biofilm formation observed upon CRISPRimediated silencing of gacS is in agreement with the regulatory model and with phenotypes observed in gacS mutants in various Pseudomonas 17,18,25,40,68 . In SBW25, GacS is also regulating genes involved in oxidative stress response, and the gacS::Tn5 mutant has a reduced capacity to survive exposure to sub-lethal doses of H2O2 25 .…”
Section: Discussionsupporting
confidence: 88%
“…fluorescens phenotypes related to mobility and biofilm are typically measured after 48 hours, we investigated CRISPRi-mediated silencing of the pleiotropic gacS (PFLU3777) gene. We found that upon induction of dCas9 expression, the strain expressing the gacSNT guide was totally impaired in swarming motility after 48 hours ( Figure 3), in keeping with the tight control of motility by gacS in Pseudomonas 17,24,25,67,68 . Expression of the gacST guide also led to a clear defect in swarming (supplementary Fig.…”
Section: Silencing Of the Two-component Sensor Kinase Gacs Impairs Mosupporting
confidence: 69%
“…; Seaton et al. ). These mutations can confer significant fitness benefits (Duffy and Défago ; Driscoll et al.…”
Section: Discussionmentioning
confidence: 98%
“…For example, loss-of-function mutations of global regulators gacA and gacS arise at high rates in the laboratory and in natural populations (Duffy and Défago 2000;van den Broek et al 2005;Driscoll et al 2011;Seaton et al 2013). These mutations can confer significant fitness benefits (Duffy and Défago 2000;Driscoll et al 2011), and lead to loss of public goods, including extracellular enzymes, antibiotics, and biofilm formation (Bull et al 2001;Seaton et al 2013), but also private goods involved in primary metabolism (Wei et al 2013). Similarly, mutations in a LysR-type regulator in Pseudomonas aureofaciens lead to an inability to produce antifungal compounds (Silby et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…As in P. aeruginosa, this system stimulates biofilm formation (Barahona et al, 2010;Cheng et al, 2013;Duque et al, 2013). Recent transcriptional profiling studies using a gacS mutant of P. fluorescens have shown that the system positively affects the expression of genes involved in exopolysaccharide synthesis, cyclic lipopeptide synthesis and c-di-GMP signalling (Cheng et al, 2013;Seaton et al, 2013). A role of the GacAS system in the regulation of motility appears to be strain-dependent (Martinez-Granero et al, 2006;Barahona et al, 2010;.…”
Section: Involvement Of Srnas In P Putida and P Fluorescens Biofilmmentioning
confidence: 97%